Comparative description of larvae of the European species of Distoleon Banks: D. annulatus (Klug, 1834) and D. tetragrammicus (Fabricius, 1798) (Neuroptera, Myrmeleontidae) - Acevedo, Fernando; Monserrat, Víctor J.; Badano, Davide (Zootaxa, 2013)
The third instar larva of Distoleon annulatus (Klug, 1834) is described for the first time and compared with the larva of the other known species of the genus in Europe: D. tetragrammicus (Fabricius, 1798). Diagnostic characters of the larvae of the genus Distoleon, as well as the interspecific differences, are provided and illustrated. Larvae of Distoleon appear to be morphologically conservative and they are mainly recognized by means of the pigmentation pattern.